29 Predicting short-term response to plantar massage in those with chronic ankle instability. (12th October 2015) - Wikstrom, EA; McKeon, PO
Abstract : Background: Plantar massage improves balance impairments associated with chronic ankle instability (CAI). However, there is no data to determine which patients with CAI would respond favourably to a plantar massage intervention. Objective: To develop a preliminary clinical prediction rule that identifies which patients with CAI would have a favourable postural control response after a 2-week plantar massage intervention. Design: Prospective cohort study. Setting: Research laboratory. Participants: Nineteen participants with self-reported CAI (age = 22.3 ± 2.8 years; height = 1.7 ± 0.8 m; body mass = 75.5 ± 14.2 kg) participated. CAI was defined as at least two episodes of "giving way" within the past 3 months (mean = 5.4 ± 4.8); scoring ≤90% on the Foot and Ankle Ability Measure (FAAM) (mean = 76.8 ± 12.9%, and scoring ≤80% on the FAAM-Sport (mean = 62.7 ± 13.6%). Interventions: Patients received 6, 5-minute plantar massage treatments over a 2-week period. Main outcome measurements: Single limb balance (SLBT) was assessed via 3, 20-second trials on a firm surface with eyes closed while errors were tracked. SLBT was recorded before, after the first treatment, and after the final treatment. A favourable response was defined as a change in the SLBT score that exceeded the minimum detectable change after the 2-week intervention. Potential predictor variables were entered into a stepwise logistic regression model to determine the most accurate set of variables for predicting treatment success. Results: 10 of the 19 participants had a favourable response (52.6%). Baseline FAAM-Sport scores >70.31% and an SLBT change of >1.67 errors after the first treatment predicted a favourable response (combined r 2 = 0.545). Both factors resulted in a 100% favourable response rate while one and no factors resulted in an 86% and 0% favourable response rate respectively. Conclusion: Preliminary results suggest that a FAAM-Sport baseline score and an immediate change in SLBT can accurately determine which CAI patients will have a favourable postural control outcome following a 2-week plantar massage intervention.